Burma, 1942 : the road from Rangoon to Mandalay - Warren, Alan (Continuum, 2011)
In December 1941 Japan set out to seize South-East Asia and the western Pacific to complete the building of a self-sufficient empire. The rapid loss of all of Britain's possessions in the Far East was the culmination of a failed attempt to deal with the rise of Japanese imperialism. Britain's bluff was called and millions of Britain's protected' subjects in Asia fell into the hands of a brutal occupying power. The British fought the Second World War in Burma and India against the backdrop of nationalist unrest and revolt. The appalling Bengal famine of 1943, brought about by the loss of Burma's rice crop and the dislocation of government, would cause the deaths of many. Alan Warren provides a new study of the series of battles that made up the Burma campaign, including first-hand accounts of the conflict and a fresh examination of the armies and commanders of the major combatants. Burma 1942 powerfully demonstrates how victory or defeat in particular battles altered the trajectory of the conflict, affecting the lives of millions.